Database design, application development and administration - Mannino, Michael V. (McGraw Hill, 2007)
Mannino's "Database Management" provides the information you need to learn relational databases. The book teaches students how to apply relational databases in solving basic and advanced database problems and cases. The fundamental database technologies of each processing environment are presented; as well as relating these technologies to the advances of e-commerce and enterprise computing. This book provides the foundation for the advanced study of individual database management systems, electronic commerce applications, and enterprise computing.